Predicting Yolk Height, Yolk Width, Albumen Length, Eggshell Weight, Egg Shape Index, Eggshell Thickness, Egg Surface Area of Japanese Quails Using Various Eggs Traits as Regressors - Alkan, Sezai; Karabag, Kemal; Galic, Askin; Balcioglu, M. Soner (International Journal of Poultry Science, 2007)
The research was conducted an eggs of Japanese quails maintained in cages at the research unit, Agricultural Faculty, University of Akdeniz, Turkey. Two hundred and forty eggs selected randomly. Egg weights (g), egg length (mm), egg width (mm), eggshell weight (g) and eggshell thickness (mm) were measured. The egg weight was better predictable from egg width and egg length. Following equation was developed to predict egg weight from egg width and length. Y = -21.658+0.828 *(X1)+0.373 * (X2). Where, Y = was predicted egg weight, X1 = egg width, X2 = egg length. Following equation was developed for predicting eggshell weight from egg weight, width and length. Y = 0.573+0.01532*(X3)+0.0238* (X4). Where, Y = was predicted eggshell weight, X3 = egg length and X4 = egg width. Egg shape index was predictable with sufficient accuracy from egg length and width and following equation was developed to predict it; Y = 0.79+0.0307*(X5)-0.02423*(X6). Where, Y = was predicted egg shape index, X5 = egg width, X6 = egg length. Eggshell surface area was better predictable from egg weight, width and length. So, following equation was developed for predicting eggshell surface area. Y = 10.561-0.178*(X7) -0.045*(X8)+1.535*(X9). Where, Y = was predictable eggshell surface area, X7 = egg width, X8 = egg length, X9 = egg weight.